The Social Process of Scientific Investigation
XXVIII, 328 p.
Keywords: practice, some of which is translated into the standard forms of public discourse, in publication, and then retranslated by readers and adapted again to local practice at self-selected other sites. Less may be left implicit, and additional personal and contextual information is carried, by the "informal" methods of communication which mediate local projects and international publication. But both methods of communication are screens as well as conduits of information. History and Background of the Volume When the planning of this volume began in the spring of 1977, it seemed a natural part of the mandate for the Yearbook. There had also been a number of more specific calls for deeper studies of research in social and historical context (3). These calls can be seen as giving permission and legitimacy to ask questions otherwise seen as irrelevant, or even disrespectful, and as attempts to develop new perspectives from which to ask and to answer them. The implied and expressed irreverence toward traditions and institutions of great respect may have prolonged this process of initial apologetics. In any case, in May 1977 the theme of 'The Social Process of Scientific Investigation' was proposed to the Editorial Board for Volume IV as "the heart of the subject. " That is, the ethnographic and detailed historical study of actual scientific activity and thinking at or close to the work site.